Pembuatan Aplikasi Chatbot Faq Untuk Motionbank - Aziz, Siti Nur Farrah; Nathasia, Novi Dian; Hassolthine, Cian Ramadhona (Journal of Information System, Applied, Management, Accounting and Research, 2024)
Currently, Frequently Asked Questions (FAQ) are used to address common questions often asked by users. However, users frequently avoid reading FAQ as they are considered less efficient in providing answers to common queries. The objective of this research is to enhance Customer Service Efficiency and provide Quick and Consistent Responses. Therefore, a FAQ Chatbot is needed to improve customer service efficiency and offer prompt responses to frequently asked questions in the MotionBank application. The FAQ Chatbot is an interactive system designed to deliver quick and accurate answers to common user queries. By utilizing artificial intelligence through Natural Language Processing methods on the Dialogflow platform, the FAQ Chatbot can automatically comprehend questions and respond with fast, relevant information, providing more responsive customer service. The research results indicate that the FAQ Chatbot application is capable of addressing frequently asked questions posed by users. The application also offers an interactive experience, responding quickly to common questions and assisting users in obtaining information related to MotionBank.